Current status and future direction of metallic and polymeric materials for advanced vascular stents - Im, Seung Hyuk; Im, Dam Hyeok; Park, Su Jeong; Jung, Youngmee; Kim, Dong-Hwee; Kim, Soo Hyun (Pergamon Press Ltd., 2022)
Cardiovascular disease (CVD) has emerged as a severe illness worldwide. Currently, the top ten causes of death in the world include ischemic heart disease according to the Global Health Observatory data provided by the World Health Organization (WHO). To treat the CVD, percutaneous coronary intervention (PCI) has been used in clinical treatment. Unfortunately, CVD is still considered a serious illness for human health, even though the mortality due to CVD has reduced compared to the time before the availability of PCI procedure. Since the implantation of the bare metal stent in humans as the first-generation stent, drug-eluting and biodegradable stents have been developed as the second-and third-generation stents to address the drawbacks of previously developed stents. Currently, various types of stents with different geometries, structures, backbone materials, and other properties have been developed, but identifying the best stent for superior clinical efficacy is still difficult. To address this issue, this review classifies the vascular stents according to four types of scaffold materials: non-degradable metal, degradable metal, nondegradable polymer, and degradable polymer. Additionally, majority of the vascular stents withvarious merits and demerits that have been developed till date are discussed with focus on the critical requirements for next-generation stents.